Improving Written Communication Skills and Mathematical Disposition of Tenth Grade IPS 4 Students by Using Think-Talk-Write (TTW) Learning Strategy at SMAN 50 Jakarta - Radiusman .; A. Noornia; L. Ambarwati (Jurnal Pendidikan Indonesia, 2019)
The aim of this research was to improve mathematical written communication and mathematical disposition of students by using think-talk-write (TTW) learning strategy in tenth grade IPS 4 students at SMAN 50 Jakarta 2017/2018 academic year. The design of this study was a classroom action research. The subject of this research consists of 6 students, 2 students with low written communication skills with moderate disposition skills, 2 students having medium-skilled and medium disposition ability and 2 students who have high disposition ability with medium and high disposition ability. The data collection techniques were consist of    1) Giving mathematics written communication ability test, 2) Spreading mathematic disposition questionnaire, 3) Doing filed notes, 4) Interviewing with the research subjects. The result was based on the end of the third cycle, it was obtained all subject experienced has increase in mathematical written communication ability and 4 out of 6 subjects experienced has increase in mathematical disposition ability. Based on the results, it can be concluded that the TTW learning strategy can increase mathematical written communication and mathematical disposition ability in tenth grade IPS 4 students at SMAN 50 Jakarta 2017/2018 academic year. In this research, an improvement made at the thinking stage was to write answers on the worksheet so that students will be more passionate about thinking of how to solve problems. On the talking stage, students were not only explaining completion but also helping team members who having difficulties. On the write stage, students could write the answer using their own phrase so that they will understand more about the completion based on observations and the results of questionnaires to increase the ability of mathematical disposition it can be seen that students experience increased self-confidence in explaining the ideas obtained, able to solve problems in various ways and have the willingness to solve mathematical problems. Besides, when the teacher asks students to re-examine the result of the work, it can be seen that students check their work while checking if there was a problem-solving problem.